Examining women leaders’ forte in localizing the sustainable development goals in Malaysia / Shahnaz Shahizan - Shahnaz , Shahizan (2018)
Malaysian women leaders have great potential to successfully implement the United Nations (UN) Sustainable Development Goals (SDG) in the country. This research aims to study the strengths that the women leaders have by investigating the relationship of variables in the localization of the SDG. The challenges faced by women leaders are expected to be substantial, such as leadership qualities needed to assure stimulation of sustainable development and inequality in the power dynamics. The researcher distributed questionnaires to 628 women leaders at the grassroots level in Malaysia. The survey includes leadership characteristics, organizational status, and gender awareness. The researcher gathered information on Malaysian leaders from the United Nations Development Programme (UNDP) in Malaysia, Ministries, and various agencies. Findings suggest that the women leaders are aware of the SDG and the relationship between the three primary variables are insignificant, and the linear regression model, seemed to be able to predict a correlation between interest in the implementation of SDG with three most significant predictors which are leadership traits, SDG activities previously implemented, and the level of gender awareness. Further research is suggested to reveal a workable universal model with more relevant variables that could be emulated by other organizations and countries. Malaysian women leaders may have a chance to pioneer a successful localization of the SDG at the grassroots level and lead the nation to be a prosperous and developed nation, recognized worldwide.